2016
DOI: 10.1016/j.athoracsur.2015.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aortic Insufficiency on Ascending Aortic Dilatation and Adverse Aortic Events After Isolated Aortic Valve Replacement in Patients With a Bicuspid Aortic Valve

Abstract: An aggressive policy of preventive aortic interventions seemed appropriate in patients with BAV-AI during AVR, and BAV phenotype presenting as either insufficiency or stenosis should be taken into consideration when contemplating optimal surgical strategies for BAV aortopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
4
34
0
Order By: Relevance
“…30 Maybe our technique of AOP was not perfect or the remaining wall tissue is less resilient in certain patients, especially in those with aortic insufficiency. 31 Because of the reoperations performed and those probably to come in the follow-up time, careful surveillance of patients undergoing AOP is necessary and the indication for AOP needs more restriction or should abandoned at all because AAR showed best results and carried minimal increased surgical risk. Nevertheless, the argument of preserving the Windkessel function with AOP may turn out later in life to be beneficial for left ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…30 Maybe our technique of AOP was not perfect or the remaining wall tissue is less resilient in certain patients, especially in those with aortic insufficiency. 31 Because of the reoperations performed and those probably to come in the follow-up time, careful surveillance of patients undergoing AOP is necessary and the indication for AOP needs more restriction or should abandoned at all because AAR showed best results and carried minimal increased surgical risk. Nevertheless, the argument of preserving the Windkessel function with AOP may turn out later in life to be beneficial for left ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have validated the significant differences in systolic aortic flow and WSS patterns between R-L and right-noncoronary (R-N) BAV patients. 10, 11 Since those with moderate-to-severe aortic insufficiency accounted for less than 10% in R-N BAV patients, 16, 26, 27 we chose R-L BAV patients as the study population for further categorization based on valve function. We found it similar to previous reports that R-L BAV patients tended to exhibit peak WSS at the right-anterior or anterior position of ascending aorta, which progressed along a right-handed helical aortic outflow until the level of supra-aortic artery.…”
Section: Discussionmentioning
confidence: 99%
“…1013 It has been demonstrated in recent cohort studies that BAV patients with aortic insufficiency tended to suffer from a higher risk for progressive ascending aorta dilatation and adverse aortic events after isolated aortic valve replacement surgery compared to their aortic stenosis counterparts. 1416 However, there is limited data on systolic aortic outflow and WSS distribution as a function of aortic valve dysfunction such as stenosis or insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Girdauskas et al found that patients with BAV-AI had a 10-fold higher risk of post-AVR aortic dissection when compared to patients with BAV-AS (Girdauskas et al, 2015b). A study by Wang et al (2016) found that patients with BAV-AI had a higher prevalence of R-L fusion phenotypes and wider aortic roots than patients with BAV-AS. Girdauskas et al (2015a) found that 34% of participants with BAV and root phenotype suffered aortic complications after AVR and only 50% of patients in the study were unburdened by aortic complications 15 years post-AVR.…”
Section: Resultsmentioning
confidence: 99%
“…Girdauskas et al reported that 3/56 patients with root phenotype expired due to type A dissection, while 0/153 patients with stenosis and ascending aortic dilation suffered a Type A aortic dissection (Girdauskas et al, 2012, 2015a). Both Girdauskas et al (2012) and Wang et al (2016) found that patients with BAV-AI and root aneurysm are closer to Marfan syndrome (MFS) pathology and have a higher risk of aortic dissection and rupture. When comparing patients with BAV and MFS, Itagaki et al (2015) found that the risk of aortic complications after AVR was 10-times higher for patients with MFS than for patients with BAV, but patients with BAV were at a significantly greater risk than patients with acquired disease of a tricuspid aortic valve.…”
Section: Resultsmentioning
confidence: 99%